The Art of Piano Transcription as Critical Commentary - Colton, David Glenn (My University, 1992)
The art of piano transcription represents a lengthy historical trend spanning musical idioms as diverse as fourteenth-century keyboard intabulations and twentieth-century recompositions. Part of the piano transcription's development has been the insightful role of the genre as a vehicle of critical commentary, a purpose which the transcription fulfils in a manner different from all other modes of music criticism. It is a commentary on one artist's ideas through the creativity of another artist in what might be described succinctly as "music about music."
A brief introductory section of the thesis documents the piano transcription's historical and terminological framework while the opening chapter describes the "practical purposes" of the genre, with emphasis on the factors contributing to the transcription's overwhelming prominence in the nineteenth century. Chapter Two discusses the artistic merit of the genre as an independent art form whose ultimate value must be judged not on preconceived biases, but rather on the intrinsic musical qualities of each work.
Chapter Three documents the critical role of the piano transcription by: 1) outlining the historical development of the genre's critical potential, 2) describing the various compositional means by which the transcriber assumes the role of critic and 3) undertaking a detailed examination of several transcriptions fulfilling this unique function, including: a) J. S. Bach's transcription of Vivaldi's Violin Concerto in 0 major, Op. III, No.9; b) Franz Liszt's transcription of the song "Moja Pieszczotka," Op. 74, No. 12, by Frederic Chopin; and c) two operatic fantasies based on Georges Bizet's Carmen - the first by Ferruccio Busoni (Chamber Fantasy on Bizet's "Carmen", and the second by Kaikhosru Shapurji Sorabji (Pastiche on The Habanera from "Carmen" by Bizet).
By altering and recomposing the original models through various compositional means, piano transcriptions offer insightful commentary on the original works. The uniquely creative means of expressing such commentary enables the transcription to reveal provocative insights into the original works which may otherwise have remained latent and unexplored. It is for this reason, perhaps more than any other, that piano transcriptions continue to be valued to the present day.
Keywords: Music; Music